Before the frost : a Linda Wallander mystery - Mankell, Henning, 1948-2015 (Mankell, Henning, 1948-2015. Kurt Wallander mystery., 2005)
"Just graduated from the police academy, Linda Wallander returns to Skane to join the police force, and she already shows all the hallmarks of her father--the maverick approach, the flaring temper. Before she even starts work she becomes embroiled in the case of her childhood friend, Anna, who has inexplicably disappeared. As the case that her father is working on dovetails with her own, something far more dangerous than either could have imagined begins to emerge. They soon find themselves forced to confront a group of extremists bent on punishing the world's sinners"--Publisher's website.